Pack aluminizing of inconel 718 superalloy produced by cold spray additive manufacturing - Bayram, Serra (Graduate School, 2025)
Inconel 718 is a nickel-based superalloy known for its excellent mechanical properties at elevated temperatures. The alloy's chemical composition includes nickel, chromium, iron, niobium, molybdenum, and titanium, which collectively determine its phase constitution and performance. The primary matrix phase is the face-centered cubic (FCC) γ (gamma) phase. The principal strengthening precipitates are γ′ (Ni₃(Al,Ti)) and γ″ (Ni₃Nb) phases. Additionally, carbides (MC, M₂₃C₆), delta (δ – Ni₃Nb) phase, and Laves phases may be present in the microstructure. The δ phase precipitates mainly at grain boundaries, contributing to grain size control. Laves phases, typically rich in niobium, form during solidification or due to improper heat treatment and are brittle phases detrimental to the alloy's ductility and impact toughness. These phases also reduce the Nb content available for γ″ precipitation hardening, thereby limiting mechanical strengthening. The distribution, quantity, and morphology of these phases directly influence the high-temperature strength, corrosion resistance, and fatigue behavior of Inconel 718. Consequently, processing parameters and heat treatment are critical for microstructural control. Traditionally, Inconel 718 is produced by casting, forging, and rolling. Recently, alternative manufacturing methods, including cold spray additive manufacturing, have emerged. Cold spray technology, originally developed for surface coating, is now applied to additive manufacturing of Inconel 718, enabling the deposition of layers at supersonic velocities and relatively low temperatures without melting. This low processing temperature preserves the initial microstructure of the substrate. Layers are sequentially deposited until the desired geometry is achieved, without melting or sintering. Additive manufacturing processes typically result in high porosity, which necessitates post-processing such as heat treatment and hot isostatic pressing to reduce porosity and improve material properties. Heat treatment also plays a crucial role in dissolving undesirable phases such as Laves phases formed during gas atomization powder production. Due to the absence of melting during cold spray, all phases present in the feedstock powder, including Laves phases, remain in the deposited microstructure. Homogenization heat treatments conducted at approximately 1150–1200 °C for several hours effectively dissolve Laves phases. Subsequent aging treatments precipitate γ″ phases, further enhancing mechanical properties. Prolonged exposure at ~900 °C promotes the formation of needle-like delta (δ) phases in the microstructure. These δ phases initially precipitate in Nb- and Mo-rich Laves regions prior to heat treatment. Surface coatings are commonly employed to enhance the high-temperature performance of superalloys like Inconel 718. Among various techniques, pack aluminizing is a widely used thermochemical diffusion process based on solid-state diffusion of aluminum into the substrate surface. During this process, aluminum-containing powder mixtures, activators, and inert carriers are placed in a sealed environment and heated at elevated temperatures. Aluminum diffuses into the substrate surface, forming Al-rich intermetallic phases. Pack aluminizing significantly improves the oxidation and hot corrosion resistance of Inconel 718 by forming a protective diffusion coating that acts as a barrier against aggressive environmental species. The diffusion coating formed after pack aluminizing consists mainly of a multilayer structure: an outer, dense, and hard β-NiAl intermetallic layer rich in aluminum, and an inner diffusion zone with lower aluminum concentration containing both Ni and Al. The β-NiAl layer provides excellent oxidation resistance at high temperatures due to its compact and continuous nature, while the diffusion zone forms a compositional gradient between the substrate γ phase and the β-NiAl layer. Minor amounts of carbides and other intermetallics may also form during the process. This coating exhibits strong adhesion to the substrate, significantly enhancing surface protection and extending service life. In this study, Inconel 718 superalloy specimens fabricated via cold spray additive manufacturing underwent homogenization heat treatment at 1200 °C for 2 hours. Porosity and hardness measurements were performed before and after heat treatment. Pack aluminizing was then applied at 600 °C for 5 hours using a powder mixture consisting of 5% AlCl₃, 25% Al, and 70% Al₂O₃. The resulting coating thickness was approximately 14 μm, confirmed by optical microscopy and scanning electron microscopy (SEM). Oxidation tests were conducted on coated and uncoated samples for durations of 24, 48, 72, and 96 hours, with weight change measurements recorded. Phase identification was performed using X-ray diffraction (XRD), and coating morphology was characterized by SEM coupled with energy-dispersive spectroscopy (EDS). SEM analyses before heat treatment revealed a highly porous and hollow microstructure with intergranular segregation between layers, which adversely affected mechanical and chemical resistance. The homogenization heat treatment significantly reduced porosity and dissolved Nb- and Mo-rich Laves phases, resulting in equiaxed grains and annealing twins. These microstructural improvements enhanced oxidation resistance and mechanical properties. Post heat treatment, a complex oxide layer composed of chromium, nickel, and oxygen formed on the surface, attributed to the exposure to open atmosphere during the heat treatment process. Beneath the oxide layer, regions enriched in niobium and molybdenum but depleted in nickel were observed. Micro-Vickers hardness tests confirmed that the oxide layer did not negatively affect the subsequent coating process. Pack aluminizing produced a continuous, compact coating with strong adherence and no detectable voids or delamination at the substrate-coating interface. Oxidation tests on uncoated samples showed formation of a Cr₂O₃ oxide layer that partially transformed into volatile CrO₃ at temperatures above 900 °C, causing weight loss and degradation. These uncoated samples exhibited poor oxidation resistance, with microcracks and porosity appearing after 96 hours of oxidation. In contrast, coated samples developed a protective Al₂O₃ oxide layer near the surface with approximately 54.2% aluminum and 43.3% oxygen content, maintaining coating integrity during oxidation. Detailed SEM analyses identified three distinct sublayers in the coating: an outer NiAl intermetallic layer, a middle NiAl-containing intermediate layer, and an inner diffusion zone. The oxidation process promoted the formation of these layers and induced Kirkendall porosity near the lower regions due to Ni, Fe, and Cr diffusion. Over time, the thickness of the outer NiAl layer decreased. After oxidation at 900 °C, needle-shaped delta phases formed within the substrate, while globular delta phases appeared in the diffusion zone, indicating diffusion-driven phase transformations. These findings demonstrate that pack aluminizing significantly enhances the oxidation resistance and microstructural stability of Inconel 718 superalloy under high-temperature conditions.
Soğuk sprey eklemeli imalat yöntemi ile üretilen inconel 718 süperalaşımının kutu alüminyumlama işlemi
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2025
Keywords: alloys; alaşımlar; inconel 718; cold sprey; soğuk sprey; pack aluminizing; kutu alüminyumlama